Translating nutritional ecology from the laboratory to the field: milestones in linking plant chemistry to population regulation in mammalian browsers. Issue 3 (12th September 2013) - DeGabriel, Jane L.; Moore, Ben D.; Felton, Annika M.; Ganzhorn, Jörg U.; Stolter, Caroline; Wallis, Ian R.; Johnson, Christopher N.; Foley, William J.
<x xml:space="preserve">Abstract</x> A central goal of nutritional ecology is to understand how variation in food quality limits the persistence of wild animal populations. Habitat suitability for browsing mammals is strongly affected by concentrations of nutrients and plant secondary metabolites (PSMs), but our understanding of this is based mostly on short‐term experiments of diet selection involving captive animals. In the wild, browsers forage in biologically, chemically and spatially‐complex environments, and foraging decisions in response to varying food quality will be correspondingly complicated. We have identified four steps that must be achieved in order to translate our understanding from laboratory experiments to populations of mammalian browsers: 1) knowing what foods and how much of these wild browsers eat, as well as what they avoid eating; 2) knowing the relevant aspects of plant nutritional and defensive chemistry to measure in a given system and how to measure them; 3) understanding the spatial distribution of nutrients and PSMs in plant communities, the costs they impose on foraging and the effects on animals' distributions; and 4) having appropriate statistical tools to analyse the data. We discuss prospects for each of these prerequisites for extending laboratory studies of nutritional quality, and review recent developments that may offer solutions for field studies. We also provide a synthesis of how to use this nutritional knowledge to link food quality to population regulation in wild mammals and describe examples that have successfully achieved this aim.